Farming Systems Approach: A Real Time Way for Sustainability and Profitability in Agriculture - Srinivas, Manukonda; Reddy, L. Rajashekara; Anusha, B. (Chronicle of Bioresource Management, 2023)
Small and marginal farmers are the core of Indian agricultural rural economy consisting 80% of total farming community but possessing only 36% of total operational land holdings. The declining per capita land availability poses a serious challenge to sustainability and profitability of these farmers. Majority of farm holdings are dry lands and even irrigated areas depends on monsoon. If farmers concentrate only on crop production, they will be subjected to high degree of unsustainability in income. Environmental degradation, depletion of soil health, unstable income of the farmer will further add to the intensity of the problem. As there is no scope for horizontal expansion of agricultural land, only alternative approach is for vertical expansion through various farm enterprises requiring less space and time, but, giving high productivity and ensuring periodic income is possible only through Integrated Farming System approach.